Comparative peculiarities of genomic diversity in Gallus gallus domesticus chickens with decorative plumage: the muffs and beard phenotype - N. V. Dementieva; Y. S. Shcherbakov; A. E. Ryabova; A. B. Vakhrameev; A. V. Makarova; O. A. Nikolaeva; A. P. Dysin; A. I. Azovtseva; N. R. Reinbah; O. V. Mitrofanova (Вавиловский журнал генетики и селекции)
Throughout history, humans have been attempting to develop the ornamental features of domestic animals in addition to their productive qualities. Many chicken breeds have developed tufts of elongated feathers that jut out from the sides and bottom of the beak, leading to the phenotype known as muffs and beard. It is an incomplete autosomal dominant phenotype determined by the Mb locus localised on chromosome GGA27. This project aimed to analyse the genetic diversity of chicken breeds using full genomic genotyping with the Chicken 60K BeadChip. A total of 53,313 Single Nucleotide Polymorphisms were analysed. DNA was obtained from breeds with the muffs and beard as a marker phenotype: Faverolles (n = 20), Ukrainian Muffed (n = 18), Orloff (n = 20), Novopavlov White (n = 20), and Novopavlov Coloured (n = 15). The Russian White (n = 20) was selected as an alternative breed without the muffs and beard phenotype. The chickens are owned by the Centre of Collective Use “Genetic Collection of Rare and Endangered Breeds of Chickens” (St. Petersburg region, Pushkin), and are also included in the Core Shared Research Facility (CSRF) and/or LargeScale Research Facility (LSRF). Multidimensional scaling revealed that the Novopavlov White and the Novopavlov Coloured populations formed a separate group. The Ukrainian Muffed and the Orloff have also been combined into a separate group. Based on cluster analysis, with the crossvalidation error and the most probable number of clusters K = 4 taken into account, the Orloff was singled out as a separate group. The Ukrainian Muffed exhibited a notable similarity with the Orloff under the same conditions. At K = 5, the populations of the Novopavlov White and the Novopavlov Coloured diverged. Only at K = 6, a distinct and separate cluster was formed by the Ukrainian Muffed. The Russian White had the greatest number of short (1–2 Mb) homozygous regions. If the HOXB8 gene is located between 3.402 and 3.404 Mb on chromosome GGA27, homozygous regions are rarely found in the chickens with the muffs and beard phenotype. Scanning the chicken genome with the Chicken 60K BeadChip provided enough information about the genetic diversity of the chicken breeds for the peculiarities of the development of the ornamental muffs and beard phenotypes in them to be understood. For example, Phoenix bantams, whose tail feathers grow throughout their lives, require greater consideration of husbandry conditions.